BUSINESS ANALYSIS USING SUSTAINABLE FAMILY BUSINESS THEORY - Firmansyah, Ardi; Wulandari, Jeni; adistya, dyang (Jurnal Kompetitif Bisnis, 2022)
ABSTRACT Ownership in a business is dominated by the family, this is a common form that is often found in various countries. This research is a descriptive study using a qualitative approach. The research was conducted in the design decoration and catering business in Bandar Lampung. Determination of the sample is done by purposive sampling technique where the criteria for the informants who will be interviewed and data taken have been determined. The results showed that: (1) Family business development was carried out in various ways, namely: Changes in company management in the second generation by separating the catering business and design decoration; Improving relationships between vendors, fellow wedding business actors and relationships with co-workers. (2) The success factors of a family business are divided into four, namely: Inner motivation is the initial foundation to become a businessman, great motivation is found in the parents and in the second generation; Support from families where children and partners provide input or ideas in the process. Support from employees is found where loyalty is given to the company; Preparation of the next generation by involving children in doing responsibilities. By involving the children it is hoped that they will have the skills and knowledge of the business; Furthermore, family relationships are a valuable asset in running a family-managed business or family business. In building family relationships, parents, children, and other families have a role to play and there is no jealousy between families. (3) The preparation of the next generation is carried out in two ways, namely: Through education: parents prepare education for their children which in the end the next generation determines their profession; Direct practice: Parents involve children in running a business for a direct form of learning. Children are responsible for the duties and responsibilities in the company and form individual personalities. Key Words : Success, Sustainability, Family Business